Illustrated dictionary of metalworking and manufacturing technology - Krar, Steve F.
This sweeping new resource provides professionals in metalworking, manufacturing, and the skilled trades with clear, concise, and practical descriptions of all technical terms specific to these technologies - from more conventional manufacturing processes and machine, hand, and cutting tools to CNC machining processes, nontraditional machining processes, welding, computer and internet applications, laser technology, and robotics.